2013
DOI: 10.1371/journal.pone.0065184
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Oxidative Stress in Occurrence of Relapses in Multiple Sclerosis: The Spectrum of Oxidatively Modified Serum Proteins Detected by Proteomics and Redox Proteomics Analysis

Abstract: Multiple sclerosis (MS) is an autoimmune inflammatory demyelinating disease of the central nervous system. Several evidences suggest that MS can be considered a multi-factorial disease in which both genetics and environmental factors are involved. Among proposed candidates, growing results support the involvement of oxidative stress (OS) in MS pathology. The aim of this study was to investigate the role of OS in event of exacerbations in MS on serum of relapsing-remitting (RR-MS) patients, either in relapsing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 55 publications
1
64
0
Order By: Relevance
“…Clusterin (CLUS) regulates complement factors, and it is involved in oxidative stress, preventing stress-induced aggregation of secreted proteins, and beyond its CIS/CDMS classification power, this protein might also be involved in multiple sclerosis as supported by results of a recent study (41). Here, we have demonstrated that this protein improves the CIS/CDMS classification power of CH3L1.…”
Section: Discussionsupporting
confidence: 61%
“…Clusterin (CLUS) regulates complement factors, and it is involved in oxidative stress, preventing stress-induced aggregation of secreted proteins, and beyond its CIS/CDMS classification power, this protein might also be involved in multiple sclerosis as supported by results of a recent study (41). Here, we have demonstrated that this protein improves the CIS/CDMS classification power of CH3L1.…”
Section: Discussionsupporting
confidence: 61%
“…The levels of oxidative stress biomarkers significantly increase during relapses but decrease during remission [21]. Oxidative stress levels in the plasma and CSF of MS patients are positively associated with the EDSS score [13,14].…”
Section: Introductionmentioning
confidence: 97%
“…In the course of the disease inflammation is decreased whereas the degeneration of the CNS progresses [1]. Several forms of MS are distinguished.…”
Section: Introductionmentioning
confidence: 99%